ASIAN COMMUNICATION EXPERIENCE IN THE MID OF CORONA PANDEMIC - Fitri Hardianti (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
This research is motivated by case that is happening right now, where the world is being hit by a virus called covid-19, this virus started in Wuhan, China. The spread of the Covid-19 virus which has reached 226 countries has caused the death toll to continue to rise. To date, the total number of Covid-19 cases worldwide stands at 505 million cases with a death toll of 6 million. Various efforts have been made by the government together with the medical team to find ways to stop virus Covid-19. One of them is by creating a vaccine that is considered capable of reducing the death rate caused by the Covid-19. Asia, as the region that was first affected by this virus and is considered the area where the Covid-19 virus emerged, certainly brings a lot of speculation and opinion from other countries. This is what is then felt by Asian students who continue their education abroad, one of which is in Egypt. Of course this has an impact on the communication experience they feel during this pandemic due to their status as students who come from countries in Asia. The purpose of this study was to determine the interpersonal communication experience experienced by Asian students who are currently in Egypt as an area affected by COVID-19.The method used in this research is qualitative with a phenomenological approach. The data collection technique used is interviews. The data analysis technique uses the Miles and Huberman interactive model analysis. And the data validity technique in this study uses source triangulation. The results of the study showed that there were unpleasant experiences experienced by Asian students where they were discriminated against as Asian and accused of causing the corona virus in Egypt. The forms of treatment received by the Asian students included being quipped when they were in public places such as on roads, markets or shopping centers. Then ridiculed sarcastically (roughly) as Corona in a public place, shunned when in public transportation and shoping centre and not even served when in food stores.